2013
DOI: 10.2320/matertrans.e-m2013804
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Transition Metal (TM: Co, Rh, Ni and Pd) Substitution for Ru on Thermoelectric Properties for Intermetallic Compound RuGa<sub>2</sub>

Abstract: The effects of substituting transition metals (TM: Co, Rh, Ni and Pd) on the Ru site with respect to the electrical conductivity and Seebeck coefficient for the binary semiconducting intermetallic compound RuGa 2 have been investigated above room temperature. Only Rh substituted RuGa 2 exhibited a higher electrical conductivity compared with undoped RuGa 2 . The sign of the Seebeck coefficient at 373 K for all doped samples is negative and their magnitudes exhibit rather large values of 150 < «S 373K « < 350 µ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 18 publications
(24 reference statements)
0
5
0
Order By: Relevance
“…Theoretical studies also predicted that t-FeAl 2 exhibits a band-gap near the Fermi level, which was explained by the 14 electrons rule or 18 − n (n = 4) electrons rule, where n is the average number of Fe-Fe bonds [5,6,[8][9][10][11][12]. Indeed, analog compounds RuAl 2 and RuGa 2 have been reported as narrow bandgap semiconductors with a high power factor, S 2 σ [7, [13][14][15][16]. From these theoretical and experimental works, it is expected that t-FeAl 2 also behaves like a semiconductor.…”
Section: Introductionmentioning
confidence: 99%
“…Theoretical studies also predicted that t-FeAl 2 exhibits a band-gap near the Fermi level, which was explained by the 14 electrons rule or 18 − n (n = 4) electrons rule, where n is the average number of Fe-Fe bonds [5,6,[8][9][10][11][12]. Indeed, analog compounds RuAl 2 and RuGa 2 have been reported as narrow bandgap semiconductors with a high power factor, S 2 σ [7, [13][14][15][16]. From these theoretical and experimental works, it is expected that t-FeAl 2 also behaves like a semiconductor.…”
Section: Introductionmentioning
confidence: 99%
“…16) Other n-type dopants (Co, Ni, Rh, and Pd) could not produce sufficient carrier numbers, mainly because of the formation of significant impurity bands. 21) These results indicate that determining impurity band formation using theoretical calculations would be a beneficial way to select a suitable dopant for tuning a material's thermoelectric properties.…”
Section: Impurity Band Engineering For Higher Thermoelectric Performamentioning
confidence: 95%
“…3) However, experimental carrier doping of RuGa 2 via transition metals substitution on the Ru site (hole doping: Re, electron doping: Ir, Rh, Co, Ni and Pd) [3][4][5] was not able to achieve the theoretically predicated ZT values. Ponnambalam et al 6) reported that carrier doping of RuGa 2 (Cr, Mn, Si and Co) below room temperature resulted in the effective mass of n-type RuGa 2 being larger than that of p-type RuGa 2 , as expected from band structure, leading to a larger absolute value of S for n-type RuGa 2 at the same doping level.…”
Section: Introductionmentioning
confidence: 96%
“…Our group has investigated thermoelectric properties of narrow band gap binary intermetallic compounds comprised of group-13 and transition metal elements using electronic structure calculations. [1][2][3][4][5] In the current study, we focus on TiSi 2 -type RuGa 2 and RuAl 2 , which are Nowotny chimney-ladder phases. These compounds have a narrow band gap, approximately 0.3 eV near the Fermi level, which leads to a high power factor, S 2 σ, in a mid-temperature range (RuGa 2 : 2.8 mW m…”
Section: Introductionmentioning
confidence: 99%